Injuries and Training Practices in Competitive Adolescent Distance Runners: A Retrospective Cross-Sectional Study - Mann, Robert H.; McKay, Carly D.; Clift, Bryan C.; Williams, Craig A.; Barker, Alan R. (Frontiers in Sports and Active Living, 2021)
Background: Distance running is one of the most popular sports around the world. The epidemiology of running-related injury (RRI) has been investigated in adults, but few studies have focused on adolescent distance runners. Objectives: (1) To provide descriptive epidemiology of RRI (risks, rates, body regions/areas, and severity) and examine the training practices (frequency, volume, and intensity) of competitive adolescent distance runners (13-18 years) in England, and (2) to describe potential risk factors of RRI. Methods: A cross-sectional study design was used. Adolescent distance runners (n = 113) were recruited from England Athletics affiliated clubs. Participants voluntarily completed an online questionnaire between April and December 2018. At the time of completion, responses were based on the participant’s previous 12-months of distance running participation. Incidence proportions (IP) and incidence rates (IR) were calculated. Results: The IP for ‘all RRI’ was 68% (95% CI: 60 to 77), while the IR was 6.3/1,000 participation hours (95% CI: 5.3 to 7.4). The most commonly injured body areas were the knee, foot/toes, and lower leg; primarily caused by overuse. The number of training sessions per week (i.e., frequency) significantly increased with chronological age, while a large proportion of participants (58%) self-reported a high level of specialisation. Conclusions: RRI is common in competitive adolescent distance runners. These descriptive data provide guidance for the development of RRI prevention measures. However, analytical epidemiology is required to provide better insight into potential RRI risk factors in this specific population.